Early-Occurring Dendritic Spines Alterations in Mouse Models of Alzheimer’s Disease Inform on Primary Causes of Neurodegeneration - Ammassari-Teule, Martine (Frontiers in Synaptic Neuroscience, 2020)
The general consensus that synaptic failure is the earliest cause of cognitive deterioration in Alzheimer’s disease (AD) has initially led to investigate structural (dendritic spines) and physiological (LTP) synaptic dysfunctions in mouse models of AD with established cognitive alterations. The challenge is now to track down ultra-early alterations in spines to uncover causes rather than disease’s symptoms. This review pinpoints dysregulations of the PSD protein network which alter the morphology and function of spines in early AD models, and hence inform on primary causes of neurodegeneration.